Specific features of cognitive skill development in athletes of situational sports - Vyacheslav Romanenko; Yrui Tropin; Leonid Podrigalo; Natalya Boychenko; Anatoly Abdula; Nataliia Sereda; Yaroslav Yatsiv (Pedagogy of Physical Culture and Sports)
Background and Study Aim. The formation of cognitive skills in athletes engaged in situational sports follows specific patterns determined by the characteristics of gameplay or competitive activity, as well as by the influence of psychophysiological and individual traits. An equally important factor in the development of cognitive skills is the training process, which incorporates specialized exercises and techniques aimed at stimulating cognitive processes, situational analysis, spatial imagination, and adaptive behavior. This study aimed to identify the peculiarities of cognitive skill formation in athletes participating in situational sports.